2010
DOI: 10.4315/0362-028x-73.8.1466
|View full text |Cite
|
Sign up to set email alerts
|

An ELISA-on-a-Chip Biosensor System Coupled with Immunomagnetic Separation for the Detection of Vibrio parahaemolyticus within a Single Working Day

Abstract: In this study, we constructed a rapid detection system for a foodborne pathogen, Vibrio parahaemolyticus, by using enzyme-linked immunosorbent assay (ELISA)-on-a-chip (EOC) biosensor technology to minimize the risk of infection by the microorganism. The EOC results showed a detection capability of approximately 6.2x10(5) cells per ml, which was significantly higher than that of the conventional rapid test kit. However, this high level of sensitivity required cultivation of the pathogen prior to analysis, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The widespread use of the current assay platform may be limited by the specific purpose of each disease marker. Although highly sensitive ELISA assays are very useful for ultra-low abundant biomarkers in terms of early-stage diagnosis 27 47 48 49 , they are not suitable for prolonged disease monitoring or predicting subsequent disease progression because of the elevated serum levels over normal ranges. Table 3 lists the broad-spectrum biomarkers that have been shown to exist with clinical values in the patient serum.…”
Section: Discussionmentioning
confidence: 99%
“…The widespread use of the current assay platform may be limited by the specific purpose of each disease marker. Although highly sensitive ELISA assays are very useful for ultra-low abundant biomarkers in terms of early-stage diagnosis 27 47 48 49 , they are not suitable for prolonged disease monitoring or predicting subsequent disease progression because of the elevated serum levels over normal ranges. Table 3 lists the broad-spectrum biomarkers that have been shown to exist with clinical values in the patient serum.…”
Section: Discussionmentioning
confidence: 99%
“…This approach can be applied to detect biomarkers within the low and medium ranges of protein concentration - [picograms per milliliter to micrograms per milliliter (as shown in Tables S4 and S5)]. To date, several studies have reported the biomarkers for multipurpose applications, such as disease monitoring, early detection, and prognosis. , Compared to our findings, most of these biomarkers could detect the target in a much higher range. ,, Although highly sensitive ELISA tests are very helpful for early detection with very-low-abundance biomarkers, they are not suitable for long-term monitoring of the disease and predicting disease progression because of their overly elevated levels in the serum. Tables S4 and S5 list the broad-spectrum biomarkers that have been shown to exist at clinical levels in patient serum.…”
Section: Discussionmentioning
confidence: 99%
“…Enzyme-linked immunosorbent assay (ELISA) is another immunological technology, which can be employed in LOC systems for rapid online detection of foodborne pathogens (Wang and Salazar, 2016;Yoon and Kim, 2012). This technology can be integrated into microchannels of LOC systems instead of the conventional micro-well plates (Seo et al, 2010). In this method, the target solution will flow continuously in the microchannels and antibodies immobilized on the surface of the microchannel can subsequently capture pathogens.…”
Section: Microfluidics Based Immunological Detection Methodsmentioning
confidence: 99%